2014
DOI: 10.1111/sms.12227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated domestic and international air travel on sleep, performance, and recovery for team sports

Abstract: The present study examined effects of simulated air travel on physical performance. In a randomized crossover design, 10 physically active males completed a simulated 5-h domestic flight (DOM), 24-h simulated international travel (INT), and a control trial (CON). The mild hypoxia, seating arrangements, and activity levels typically encountered during air travel were simulated in a normobaric, hypoxic altitude room. Physical performance was assessed in the afternoon of the day before (D - 1 PM) and in the morni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 37 publications
3
85
1
1
Order By: Relevance
“…Importantly, short–term, 1-h measures were able to clearly identify the acute stress prior to, during and post-flight with significant changes and moderate to large effects (ES). Taken together, our results demonstrated that a commercial flight of only 1 h exposed travelers to a high allostatic load (McEwen and Seeman, 1999; Tonello et al, 2014), which exerted considerable neural and cardiovascular stress (Brundrett, 2001; Fowler et al, 2015). Furthermore, these stress-induced responses were capable of inducing alterations in the circadian rhythms such as blood pressure (Hansen et al, 2010), that can be maintained up to 2 h after the flight.…”
Section: Discussionsupporting
confidence: 55%
“…Importantly, short–term, 1-h measures were able to clearly identify the acute stress prior to, during and post-flight with significant changes and moderate to large effects (ES). Taken together, our results demonstrated that a commercial flight of only 1 h exposed travelers to a high allostatic load (McEwen and Seeman, 1999; Tonello et al, 2014), which exerted considerable neural and cardiovascular stress (Brundrett, 2001; Fowler et al, 2015). Furthermore, these stress-induced responses were capable of inducing alterations in the circadian rhythms such as blood pressure (Hansen et al, 2010), that can be maintained up to 2 h after the flight.…”
Section: Discussionsupporting
confidence: 55%
“…The negative effects of long international travel on sleep (i.e. reduced sleep duration and efficiency and greater awakenings duration) have been documented [110]. Players who join their national team for international competition or travelling to pre-season training camps may be exposed to the negative effects of travel across multiple time zones on sleep [9].…”
Section: Travelmentioning
confidence: 98%
“…Travel fatigue is a complex summation of physiologic, psychologic, and environmental factors that accrue during an individual trip, such as prolonged exposure to mild hypoxia and cramped conditions with restricted activity [110,111]. Several studies have assessed the acute effects of short-haul air travel without crossing time zones (total travel time between 3-5 h) on performance and perceptual measures among team sport players [101,110,112]. Globally, results showed that travel has no effect on indicators of performance (i.e.…”
Section: Travelmentioning
confidence: 99%
“…Such misalignment is often present in athletes who travel rapidly across time zones [26,27], but may also occur systemically in morning-type or evening-type athletes who are forced to train or compete outside their biological, endogenous sleep window. There are both biological and behavioral aspects to circadian phase preference or "chronotype" [28,29].…”
Section: Introductionmentioning
confidence: 99%